2022
DOI: 10.1002/adma.202203888
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Negative Differential Resistance and High Tunneling Current Density in GeSn Esaki Diodes

Abstract: distribution. Novel devices with different operational principles for a sharper SS than 60 mV per decade have been extensively investigated, such as impact ionization MOS (I-MOS) transistors, [1] negative-capacitance field-effect transistors (NC-FETs), [2] or tunnel field-effect transistors (TFETs). [3] While an SS of sub-60 mV per decade has been demonstrated for those devices, the issues of the required high gate biases for I-MOS transistors or the hysteresis for NC-FETs are critical issues for the reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In 2021, Tai et al demonstrated even larger SOC strengths in GeSn [30] than in Ge [26]. With its direct-bandgap characteristics [31] and high carrier mobility [32,33], GeSn is a promising enabler to accomplish a full-functional chip including spintronic, photonic, and electronic devices compatible with the Si CMOS platform.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Tai et al demonstrated even larger SOC strengths in GeSn [30] than in Ge [26]. With its direct-bandgap characteristics [31] and high carrier mobility [32,33], GeSn is a promising enabler to accomplish a full-functional chip including spintronic, photonic, and electronic devices compatible with the Si CMOS platform.…”
Section: Introductionmentioning
confidence: 99%